Feasibility of Neuromuscular Electrical Stimulation for Gait Improvementin Post-Stroke Hemiplegia- A Case Series From an Outpatient Neurorehabilitation Unit (Indian Journal of Physiotherapy and Occupational Therapy - An International Journal, 2026)
BackgroundPost-stroke hemiplegia significantly impairs gait and mobility, particularly in outpatient settings with limited access to advanced rehabilitation technologies. Neuromuscular Electrical Stimulation (NMES) may offer a feasible adjunct to conventional physiotherapy.Methods and materialsThis prospective case series included 20 outpatients (mean age: 51.7=/- 5.6 years; stroke onset: 6-12 months) with moderate gait dysfunction (Wisconsin Gait Scale ≥26). Participants received 4-week intervention combining NMES targeting the tibialis anterior and hamstrings with conventional physiotherapy. Gait quality and functional mobility were assessed using the Wisconsin Gait Scale (WGS) and Timed Up and Go (TUG) test respectively. Data was analyzed using Wilcoxon signed-rank tests, with 95% confidence interval reported.ResultsMedian WGS scores improved from 24.5 to 18.97 (p< 0.001; 95% CI: 4.375-6.515), and  mean TUG scores decreased from 21.05s to 17.4s (p
Keywords: Stroke rehabilitation, NMES, Wisconsin Gait Scale, Timed-Up and Go Test, low-resource setting